Pertanggungjawaban Notaris Terhadap Akta Otentik yang Memuat Keterangan Palsu Ditinjau dari UU No.2 Tahun 2014 tentang Jabatan Notaris - Irawan, Tulus; , Darsono, S.H.,M.Hum (2017)
The Notary Responsibilty about official document based on false information should be regulated in the Notary Authority 2 of 2014 about concerning Notary . Faculty of Law. Muhammadiyah University of Surakarta. 2017. Notary is one of profession in law that associated with evidence in the form of official document, The notarial deed can be used as strong evidence that if sometime there is a dispute between the part or there is a lawsuit in civil and in criminal charges from other part. In Law notary not be clearly how a notary accountable legally if he made a mistake in a deed that he make, so that the problem is how accountability notary as a public and validity than products in the deed when include information in made deed by UU No.33 of 2004 amendments to the law UU 2 of 2014 concerning Notary.This type of research is kind of normative law or can be called the doctrinal law research, which focused on written rules (law in book). Data analysis was performed by collecting primary data and secondary data, which further results is described by qualitative using interpretation and logic so it can had a new plan or can be consolidate plan to answered problems.